Kejadian Nyaris Cidera (KNC) Pada Pelayanan Resep Pasien Poli Penyakit Dalam di Instalasi Farmasi Rawat Jalan RS Roemani Muhammadiyah Semarang - Octasari, Paulina Maya; Yulia, Rika; Rukminingsih, Fef (Jurnal Farmasi & Sains Indonesia, 2023)
The paradigm changing in health care form “quality” to “quality and safety” aims to improve the quality of life of patient. One of the efforts is to minimize the occurrence of incidents. The largest number of the patient safety incidence is Nearly Injury Incidence, which is 18.53%. The increased risk of NPC can be caused by their presence of polypharmacy. Polypharmacy is often experienced in patients at the Internal Medicine Polyclinic at Roemani Muhammadiyah Semarang Hospital. Therefore, it is necessary to conduct research to determine the number of KNCs in the prescription service of poly internal medicine patients in the Outpatient Pharmacy Installation of Roemani Muhammadiyah Hospital Semarang. The study was a descriptive observational study with prospective data from prescription services for patients with internal medicine at the Outpatient Pharmacy Installation of Roemani Muhammadiyah Hospital Semarang in March 2020. Evaluations were carried out at each stage of prescription service. Stages consist of prescribing, taking drugs, and preparing medicines etiquette, checking. Data were analyzed and grouped according to the type of KNC at each stage of prescription service for patients with internal medicine, the number and percentage of KNC on each prescription sheet. The results showed that there were 25 KNCs on 375 sheets of prescribed poly patients in internal medicine at Roemani Muhammadiyah Hospital Semarang. The percentage of KNC is the drug entry stage of 9 KNC (2.4%), the taking stage of 15 KNC (4%), the preparation stage of 1 KNC (0.27%).